A case of predation of Chacophrys pierottii (Anura: Ceratophryidae) by Philodryas psammophidea (Squamata: Dipsadinae) in the chacoan saltflats of central Argentina - Pereyra, Laura Cecilia (2013)
A case of predation of Chacophrys pierottii (Anura: Ceratophryidae) by Philodryas psammophidea (Squamata: Dipsadinae) in the chacoan saltflats of central Argentina.